2001
DOI: 10.1116/1.1352727
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy investigation of sidewall passivation films formed during gate etch processes

Abstract: Articles you may be interested in X-ray photoelectron spectroscopy analysis of the effect of temperature upon surface composition of InP etched in Cl2-based inductively coupled plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 9 publications
2
49
0
Order By: Relevance
“…In-depth investigation has been carried out in the past decade to explain the anisotropy of this process, and it was demonstrated that the etching of sub-100-nm Si gate was possible due to the deposition of a SiOCl or SiOBr passivation layer on the gate sidewall. 14,15 Moreover, it was reported that the use of HBr in the gas mixture significantly improves the process, 16 the exact physicochemical origin of this effect being not yet well explained to our knowledge.…”
Section: Processmentioning
confidence: 94%
See 2 more Smart Citations
“…In-depth investigation has been carried out in the past decade to explain the anisotropy of this process, and it was demonstrated that the etching of sub-100-nm Si gate was possible due to the deposition of a SiOCl or SiOBr passivation layer on the gate sidewall. 14,15 Moreover, it was reported that the use of HBr in the gas mixture significantly improves the process, 16 the exact physicochemical origin of this effect being not yet well explained to our knowledge.…”
Section: Processmentioning
confidence: 94%
“…It was indeed reported from x-ray photoelectron spectroscopy ͑XPS͒ analysis of the sidewalls of poly-Si patterns etched with Cl 2 -HBr-O 2 gas mixtures that Cl or Br desorption and substitution by oxygen take place under air exposure. 16 However, it should be considered that oxygen in the plasma can also come from the sputtering of the inner parts of the reactor, especially in our very low pressure conditions since decreasing the pressure leads to an increase of the plasma potential as observed from separate Langmuir probe measurements. 17 Moreover, as seen from the results obtained when O 2 is added in situ to the gas mixture, only a very small proportion of oxygen is sufficient to increase the O atomic concentration in the redeposition layer.…”
Section: O 2 Additionmentioning
confidence: 95%
See 1 more Smart Citation
“…The plasma chemistry used for polysilicon etching in this study is HBr/Cl 2 . As mentioned earlier, when etching with HBr/O 2 or Cl 2 /HBr/O 2 plasmas, or with addition of a small amount of oxygen to the Cl 2 plasma, the bottom of the polysilicon trenches became bumpy and the etch rates were nonuniform (Denton and Wallace, 1992;Desvoivres et al, 2001;Guinn et al, 1995;Lehmann and Widmer, 1980). Their XPS analyses reveal that the deposit is mainly either SiO x Cl y or SiO x Br y .…”
Section: Area Percentage Of the Different Components Of The C 1s Gausmentioning
confidence: 88%
“…Moreover, the difficulty of the etched products to be diffused out from the line arrays may be attributable to the microloading effects as well (Plummer et al, 2000). Interestingly, Desvoivres et al (2001) found the tapered thickness of the SiO 2 passivation layers on the sidewall of the Si-gate features when etched in HBr/O 2 high-density plasmas. That is, the passivity is not uniform through the sidewall of the features.…”
Section: Area Percentage Of the Different Components Of The C 1s Gausmentioning
confidence: 97%